2021
DOI: 10.1158/1078-0432.ccr-21-0856
|View full text |Cite|
|
Sign up to set email alerts
|

KRAS Inhibitor Resistance in MET-Amplified KRASG12C Non–Small Cell Lung Cancer Induced By RAS- and Non–RAS-Mediated Cell Signaling Mechanisms

Abstract: Purpose: Treatment with KRASG12C inhibitors such as sotorasib can produce substantial regression of tumors in some patients with non–small cell lung cancer (NSCLC). These patients require alternative treatment after acquiring resistance to the inhibitor. The mechanisms underlying this acquired resistance are unclear. The purpose of this study was to identify the mechanisms underlying acquired sotorasib resistance, and to explore potential treatments for rescuing patients with sotorasib-resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…In the preclinical setting, Suzuki et al exposed mutant KRAS G12C cells to sotorsaib finding MET amplifications in resistant cells. To further confirm this as the resistance mechanisms, they demonstrated thar after MET knockdown using siRNA, cells recovered sensitivity to sotorasib (46). Moreover, they found that MET amplified cells had higher levels of GTP-bound (active) RAS, mainly in other isoforms such as NRAS, suggesting that MET amplification could confer resistance by the reactivation of RAS-BRAF-MEK-ERK pathway by direct activation of other RAS isoforms.…”
Section: Off-target Mechanismsmentioning
confidence: 93%
See 2 more Smart Citations
“…In the preclinical setting, Suzuki et al exposed mutant KRAS G12C cells to sotorsaib finding MET amplifications in resistant cells. To further confirm this as the resistance mechanisms, they demonstrated thar after MET knockdown using siRNA, cells recovered sensitivity to sotorasib (46). Moreover, they found that MET amplified cells had higher levels of GTP-bound (active) RAS, mainly in other isoforms such as NRAS, suggesting that MET amplification could confer resistance by the reactivation of RAS-BRAF-MEK-ERK pathway by direct activation of other RAS isoforms.…”
Section: Off-target Mechanismsmentioning
confidence: 93%
“…A main mechanism of primary resistance is feedback reactivation mediated by multiple RTKs, leading to preclinical research aiming to combine the inhibition of KRAS G12C and other RTKs such as EGFR, FGFR, and MET (56). In this setting the combination of sotorasib and MET inhibitors such as crizotinib and capmatinib has shown to overcome resistance to KRAS G12C inhibitors in vitro in cancer cells with MET amplification (46). One of the main focuses of current development is targeting transduction molecules situated downstream from RTKs such as SHP2 and SOS1 which after phosphorylation favor de GTP-bound state thus activating the ERK pathway (57).…”
Section: Therapeutic Strategies For Kras G12c Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Ras—a small-molecule GTPase member—has important regulatory functions in cell signal transduction, cytoplasmic skeletal construction, and material transport ( Ostrem et al, 2013 ; Lim et al, 2014 ; Lito et al, 2016 ). Notably, recent findings indicated that the Ras gene was mutated in more than 30% of HCC-afflicted patients sampled ( Guichard et al, 2012 ; Lindsay and Blackhall, 2019 ; Suzuki et al, 2021 ). Mutations in the Ras gene have also been detected in various other types of cancers as well, including those for lung cancer, pancreatic cancer, and colon cancer ( Zhang et al, 2018 ; Zhao et al, 2018 ; Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ras-a small-molecule GTPase member-has important regulatory functions in cell signal transduction, cytoplasmic skeletal construction, and material transport (Ostrem et al, 2013;Lim et al, 2014;Lito et al, 2016). Notably, recent findings indicated that the Ras gene was mutated in more than 30% of HCC-afflicted patients sampled (Guichard et al, 2012;Lindsay and Blackhall, 2019;Suzuki et al, 2021). Mutations in the Ras gene have also been detected in various other types of cancers as well, including those for lung cancer, pancreatic cancer, and colon cancer (Zhang et al, 2018;Zhao et al, 2018;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%